Kurikulum Merdeka Belajar-Kampus Merdeka Perspektif Pendidikan Humanis Religius - Nurani, Qoim; Rizal, Dimas Ahmad; Zani, Moh. Zodikin; Thontowi, Zulkifli Syauqi (Lembaga Sosial Rumah Indonesia, 2023)
Curriculum is an inseparable part of the education system. This study will analyze the Merdeka-Merdeka Campus Curriculum Learning from a Humanist-Religious Perspective (Study of the MPI Curriculum of UIN Sunan Kalijaga Yogyakarta). This research is a field research with a descriptive-qualitative approach. Research subjects used purposive sampling. Data collection was carried out by observation, interviews and documentation. Data analysis using data reduction and data presentation. Test the validity of the data using triangulation. The results of his research show that MBKM gives freedom to students to take programs according to their talents and interests, and encourages link and match. The MBKM curriculum is in line with the theory of religious humanist education both in terms of goals, learning processes, methods and evaluation. Because students can express their ideas and thoughts into a program that is of value to society.